Intra-tympanic injections in Meniere's disease - Ologe FE (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2017)
Meniere's disease is a relatively common, sometimes disabling, disease. Pre-referral anti-vertiginous medication is common practice among family physicians. The objective of this review is to present the next level treatment of Meniere disease, beyond conservative management. Major databases such as the Pubmed were searched for recent publications on the management of Meniere's disease. The findings emphasised that the use of intra-tympanic steroid injections, among other measures, is an extensively researched treatment modality for Meniere's disease that is unresponsive to conservative management. In conclusion, referring physicians need to go beyond anti-vertiginous medications which family physicians usually prescribe. Aside from other medical treatments, intra-tympanic steroid injection is a simple, safe and reliable treatment option which needs to be further deployed in developing world practice.